Retention and viral suppression of newly diagnosed and known HIV positive pregnant women on Option B+ in Western Kenya. Issue 3 (4th March 2019) - Akama, Eliud; Nimz, Abigail; Blat, Cinthia; Moghadassi, Michelle; Oyaro, Patrick; Maloba, May; Cohen, Craig R.; Bukusi, Elizabeth A.; Abuogi, Lisa L.
ABSTRACT: Kenya introduced universal antiretroviral treatment (ART) for pregnant and breastfeeding women living with HIV (Option B+) in 2014. A retrospective study was conducted to review consecutive records for HIV positive pregnant women presenting for antenatal care (ANC) at five clinics in western Kenya. Known positive women (KP :HIV diagnosis prior to current pregnancy) were compared to newly positive (NP) women regarding virologic suppression and retention in care. Among 165 women included, 71 (43%) NP and 94 (57%) KP, NP were younger (24.5 years (SD 4.6) vs. 28.1 years (SD 5.6) compared to KP ( p < .001). Almost all NP (97%) were initiated on Option B+ while over half of KP (59%) started ART for clinical/immunological criteria ( p < .0001). KPs were more likely than NPs to have a VL performed following Kenyan guidelines (64% vs. 31%; p < .001). Among those tested, virologic suppression was high in both groups (92% KP vs. 100% NP; p = .31). More KPs (82%) vs. NPs (66%) remained active in care at 15–18 months of follow-up ( p = .02). Women newly diagnosed with HIV during pregnancy show poorer uptake of VL testing and worse retention in care than those diagnosed prior to pregnancy.